ZONE OF SACRED SPACE: THE TOMBS OF SUNAN BONANG TUBAN AND PANOPTIC AS CONSCIOUSNESS EDUCATION - Ghozi, Ahmad; Purwasito, Andrik; Warto, Warto; Rais, Wakit Abdullah (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The sacred courtyard at the tomb of Sunan Bonang Tuban is a zone based on geographical location and the level of sanctity within the tomb courtyard, which is divided into three zones. These zones are spatially divided into three parts: the first is the Jaba courtyard, the second is called the Jaba Tengah courtyard, while the third courtyard is referred to as Jeroan. All three courtyards are sacred and possess different levels of sanctity, each marked by a panoptic sign as a surveillance system. The panoptic system indirectly serves as a consciousness education for pilgrims, aiming to protect cultural heritage objects and maintain the sanctity of the tomb area. Through the panoptic system and the signs, pilgrims are encouraged to behave obediently and consciously. This research aims to describe the zones of the sacred courtyard and behavioral education through the panoptic system in the tomb courtyard of Sunan Bonang using a qualitative ethnographic research model. Data is obtained through a combination of historical methods, observation, and interviews, accompanied by Michel Foucault's panoptic theory. The findings reveal three sacred courtyard zones in the tomb of Sunan Bonang Tuban, resembling the concept of sacred places based on the Tri Loka concept, which states that the world consists of Bhur Loka (lower realm), Bwah Loka (middle realm), and Swa Loka (upper realm). In addition to the panoptic system, these three realms within the zones also provide education to pilgrims visiting the tomb of Sunan Bonang Tuban.